2015
DOI: 10.1016/j.ypmed.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

A literature review on prevalence of gender differences and intersections with other vulnerabilities to tobacco use in the United States, 2004–2014

Abstract: This report describes results from a systematic literature review examining gender differences in U.S. prevalence rates of current use of tobacco and nicotine delivery products and how they intersect with other vulnerabilities to tobacco use. We searched PubMed on gender differences in tobacco use across the years 2004–2014. For inclusion, reports had to be in English, in a peer-reviewed journal or federal government report, report prevalence rates for current use of a tobacco product in males and females, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
71
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(90 citation statements)
references
References 58 publications
(103 reference statements)
12
71
0
7
Order By: Relevance
“…The present study was conducted to follow up on observations reported as part of a literature review on gender differences where risk for cigarette smoking appeared to change in a cumulative and summative manner when gender was considered in combination with other co-occurring risk factors (Higgins et al, 2015). The present results confirm those earlier observations and extend them to additional risk-factor combinations beyond gender.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study was conducted to follow up on observations reported as part of a literature review on gender differences where risk for cigarette smoking appeared to change in a cumulative and summative manner when gender was considered in combination with other co-occurring risk factors (Higgins et al, 2015). The present results confirm those earlier observations and extend them to additional risk-factor combinations beyond gender.…”
Section: Discussionmentioning
confidence: 99%
“…DHHS, 2014). We know of no exhaustive set of risk factors for cigarette smoking, although gender, age, race/ethnicity, educational attainment, poverty status, substance use disorders, and mental illness are each well documented in the literature and are examined in the present study (Fiore et al, 2008; Higgins et al, 2015; Higgins and Chilcoat, 2009; Schroeder and Koh, 2014). While each of these risk factors inevitably co-occurs with some arrangement of the others (i.e., gender always co-occurs with chronological age, educational attainment, and race/ethnicity), there has been relatively little research reported explicitly characterizing the combined effects of co-occurring risk factors for cigarette smoking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Department of Health and Human Services, 1980), and while men’s smoking began to fall in the second half of the 1950s, women’s smoking continued to increase until the mid 1960s and did not decrease substantively until the start of the 1970s (Schuman, 1977). Although smoking prevalence started to decline earlier in men than women, U.S. men remain more likely to be smokers than women (Higgins et al, 2015; U.S. Department of Health and Human Services, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Complimenting the observations of Leventhal and colleagues on socioeconomic status as a risk factor for cigarette smoking and other substance use, my colleagues and I (Higgins et al, 2015–in this issue) contribute a systematic literature review documenting a pervasive influence of male gender as a risk factor for tobacco use. However, the Higgins et al review also examines how gender intersects with other risk factors including socioeconomic status, psychiatric status, race, among other risk factors for tobacco use.…”
Section: Physical Inactivity Obesity Cigarette Smoking and Other Tobamentioning
confidence: 98%